2016
DOI: 10.1093/brain/aww116
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenate retards epileptogenesis in acquired epilepsy models reversing changes in protein phosphatase 2A and hyperphosphorylated tau

Abstract: There are no treatments in clinical practice known to mitigate the neurobiological processes that convert a healthy brain into an epileptic one, a phenomenon known as epileptogenesis. Downregulation of protein phosphatase 2A, a protein that causes the hyperphosphorylation of tau, is implicated in neurodegenerative diseases commonly associated with epilepsy, such as Alzheimer's disease and traumatic brain injury. Here we used the protein phosphatase 2A activator sodium selenate to investigate the role of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 54 publications
4
147
0
Order By: Relevance
“…Moreover, we have previously found increased expression of pS198 and pS262 after a severe TBI (Shultz et al, 2015c). Tau-5 is a marker for total tau levels (Liu et al, 2016;Shultz et al, 2015c). Therefore, the blots on PVDF were developed with anti-pS198 (1:1000; Abcam, UK), anti-pS262 (1:1000; Abcam, UK), and antiTau-5 (1:1000, Millipore, USA), as we well as anti-PR55 (1:1000, Millipore, USA), anti-PP2Ac (1:1000; Millipore, USA), and anti-GAPDH (1:5000; Cell Signaling, USA) primary antibodies overnight at 4 C. They were then incubated with secondary antibodies of respective animal species conjugated to horseradish peroxidase and visualized by enhanced chemiluminescent substrate kit (Amersham™ ECL™ Western-blotting detection reagents) and exposure to x-films.…”
Section: Western-blottingmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, we have previously found increased expression of pS198 and pS262 after a severe TBI (Shultz et al, 2015c). Tau-5 is a marker for total tau levels (Liu et al, 2016;Shultz et al, 2015c). Therefore, the blots on PVDF were developed with anti-pS198 (1:1000; Abcam, UK), anti-pS262 (1:1000; Abcam, UK), and antiTau-5 (1:1000, Millipore, USA), as we well as anti-PR55 (1:1000, Millipore, USA), anti-PP2Ac (1:1000; Millipore, USA), and anti-GAPDH (1:5000; Cell Signaling, USA) primary antibodies overnight at 4 C. They were then incubated with secondary antibodies of respective animal species conjugated to horseradish peroxidase and visualized by enhanced chemiluminescent substrate kit (Amersham™ ECL™ Western-blotting detection reagents) and exposure to x-films.…”
Section: Western-blottingmentioning
confidence: 89%
“…Previous experiments from our laboratories have demonstrated that a continuous subcutaneous dose of 1 mg/kg/day (delivered via a subcutaneous pump) activates PP2A/PR55, reduces h-tau, and does not have any overt toxic effects in rodents (Liu et al, 2016;Shultz et al, 2015c). Furthermore, similar doses and treatment durations have been well-tolerated in human clinical trials (i.e., up to 90 mg per day for adult patients; Corcoran et al, 2010a), and a continuous dose is necessary to maintain consistent bioavailability because sodium selenate has a short half-life in vivo (approximately 1.2e2.9 h; Corcoran et al, 2010a).…”
Section: Experimental Groupsmentioning
confidence: 97%
See 1 more Smart Citation
“…63 In a murine model of Alzheimer disease, the reduction of pTau levels corresponded to decreased electroencephalographic seizures. 69 These results support pTau as a common component of neurodegenerative diseases, including acquired epilepsies. 69 These results support pTau as a common component of neurodegenerative diseases, including acquired epilepsies.…”
Section: Box 2: Ptau Accumulation and Neuronal Hyperexcitabilitymentioning
confidence: 52%
“…For the study of acquired epilepsy, the two most common used models are the post–status epilepticus (SE) model and the traumatic brain injury–induced posttraumatic epilepsy (PTE) models . Conversely, Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and Wistar Albino Glaxo from Rijswijk (WAG/Rij) are the most widely used models to study genetic generalized epilepsy with absence seizures .…”
Section: Introductionmentioning
confidence: 99%